O uso de recursos didáticos na prática pedagógica: contribuições do Stop Motion para o ensino de biologia - Macedo, Cibele Dantas (2020)
In face of the currently social difficulties, its absolutely necessary that education contributes more efficiently not only to students’ formation as well as a consciousness and actives citizens. In addition, it is expected from professionals and researchers in education the development and improvement of innovative methods on learning. These methods should allow learners’ curiosity and help them to build their learning and not just be observers on this process. In this perspective, several technological resources may be incorporated in the classroom including films and videos production with scientific content.The present dissertation aims to compare the efficiency in learning based on two strategies: 1) the expositive classes and 2) an active methodology consisting of investigative activities resulting on short animated videos production using a photographic technique named Stop Motion. More specifically, we compared the development of attitudinal, conceptual, and procedural dimensions of the knowledge between the two methodologies. This is research action based on a qualitative/quantitative approach. Data collection was based in different techniques: participant observation, pre and post questionnaire, focal group and check list. The research was developed with eight six graduating High School students in a Public School in the city of Campina Grande state of Paraiba. There was no difference in the conceptual learning between the two methodologies carried out, however, the active methodology was more valuable in many procedures’ application and attitudinal parameters execution, such as; interest, autonomy, tolerance, consciousness and collaboration. As a product of this research we developed a Didactic Guidebook to assist teachers. The product can be adapted to different realities and teaching levels.